Radikalisme dan Terorisme di Indonesia dari Masa ke Masa (Tinjauan dari Perspektif Kewarganegaraan) - Yosaphat Haris Nurasarastriya (PAX HUMANA, 2015)
Abstract"Radicalism and terrorism occurred in Indonesia from time to time with different motif, backgrounds, and display. Viewed from the perspective of citizenship radicalism, terrorism is a concept that includes how to think, and behave. One study based on the perspective of citizenship is about thinking of citizenship itself. It is closely related to the three elements of civic knowledge, civic skills, and civic virtue. Radicalism and terrorism viewed from the perspective of citizenship is a problem in a democracy and state of law. Each country demanded democracy and legal state principles of democracy while the principles of law will bring good life together as a nation or state.Keywords: Radicalism, Terrorism, Perspective, Citizenship